White adipose tissue inflammation and cancer‐specific survival in patients with squamous cell carcinoma of the oral tongue. Issue 24 (10th August 2016) - Iyengar, Neil M.; Ghossein, Ronald A.; Morris, Luc G.; Zhou, Xi K.; Kochhar, Amit; Morris, Patrick G.; Pfister, David G.; Patel, Snehal G.; Boyle, Jay O.; Hudis, Clifford A.; Dannenberg, Andrew J.
Abstract : BACKGROUND: Obesity is associated with increased adipose tissue in the tongue. Chronic white adipose tissue (WAT) inflammation commonly occurs in the obese. We investigated whether WAT inflammation in the tongue impacts survival in patients with squamous cell carcinoma (SCC) of the oral tongue. METHODS: In a retrospective cohort study, patients with T1 and T2 SCC of the oral tongue who underwent curative‐intent resection were included. Tongue WAT inflammation was defined by the presence of dead or dying adipocytes surrounded by macrophages forming crown‐like structures. The primary and secondary endpoints were disease‐specific survival (DSS) and overall survival (OS), respectively. Subgroup analyses were carried out in patients without lymph node involvement for whom adjuvant therapies were not indicated. RESULTS: Archived tissue was available from 125 patients. The median follow‐up was 55 months (range, 3‐156 months). Overall, 49 of 125 patients (39%) had tongue WAT inflammation, which was associated with higher body mass index, increased tumor thickness, and vascular invasion ( P  < .05). The 3‐year DSS rate for patients with tongue WAT inflammation was 59% (95% confidence interval [CI], 46%‐76%) versus 82% (95% CI, 73%‐92%) for those without inflammation. For patients without lymph node involvement for whom adjuvant therapy was not indicated (N = 70), tongue WAT inflammation was associated with shortened DSS and OS ( P  < .05). When adjusted for body mass index and potential prognostic covariates, the hazard ratio for DSS and OS was 5.40 (95% CI, 1.20‐24.26) and 2.97 (95% CI, 1.02‐8.65), respectively. CONCLUSIONS: Tongue WAT inflammation is associated with worse DSS and OS in patients who have early stage SCC of the oral tongue. Cancer 2016;122:3794–3802. © 2016 American Cancer Society. Abstract : In patients with squamous cell carcinoma of the oral tongue, inflammation of tongue adipose tissue is an independent predictor of worse disease‐specific survival. In those without lymph node involvement who are currently classified as having low‐risk disease, tongue adipose tissue inflammation is correlated with shortened disease‐specific and overall survival.